2012
DOI: 10.1097/mej.0b013e328347a2aa
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness affects the quality of single operator cardiocerebral resuscitation in healthcare professionals

Abstract: Objective Sustained external chest compressions during cardiocerebral resuscitation (CCR) are physically demanding. It might be hypothesized that a high cardiopulmonary exercise capacity and/or muscle strength delays the development of physical fatigue and, consequently, preserves CCR quality. We intended to assess the impact of cardiopulmonary exercise capacity and muscle strength on CCR quality.Methods Fifteen healthcare professionals (10 men and five women, mean age 34 ± 9 years) performed a 15-min hands-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 30 publications
4
33
2
1
Order By: Relevance
“…The authors of this study are aware of the fact that it would be difficult to preselect candidates for the profession of a medical rescuer. However, according to the findings of this article and other sources [7,8,9], it would be advisable to preferably accept well-built candidates of a certain body fitness. Inefficient chest compression depth is difficult to be objectively justified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this study are aware of the fact that it would be difficult to preselect candidates for the profession of a medical rescuer. However, according to the findings of this article and other sources [7,8,9], it would be advisable to preferably accept well-built candidates of a certain body fitness. Inefficient chest compression depth is difficult to be objectively justified.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been pointed out that the increasing fatigue of the rescuer has an impact on the quality of chest compression and may be difficult to perform by physically unprepared individuals who do not always have the sufficient skills [7,8,9,10]. The 2010 AHA guidelines emphasize a compression rate of at least 100/min and a compression depth of at least 2 inches (5 cm) [1,6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Hasegawa et al [11] showed that increased fatigue led to falling quality of chest compressions in a lighter body weight group among 18 nurses. Hansen et al [12] observed 15 health care professionals in a 15-minute handson CPR session on a manikin and demonstrated significant correlations between chest compression quality and body height in addition to physical fitness and muscle strength. In contrast, Ock et al [13] found that muscle strength was the only factor affecting CPR quality among 47 participants.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, factors associated with the rescuer's ability to perform high-quality chest compressions are of major concern. Previous studies have identified several factors associated with CPR quality, including the rescuer's body weight, body height, physical fitness, and muscle strength [11][12][13]. Hasegawa et al [11] showed that increased fatigue led to falling quality of chest compressions in a lighter body weight group among 18 nurses.…”
Section: Introductionmentioning
confidence: 98%
“…European Resuscitation Council (ERC) guidelines have acknowledged this evidence and recommend a switch of rescuers every 2 min [1]. CC quality has been related to the upper extremity and trunk strength [11][12][13], but no studies have been done to ascertain the effect of power training specifically designed to increase the strength of the muscles used in CPR.…”
Section: Introductionmentioning
confidence: 99%